EFEKTIVITAS PT. PEGADAIAN DALAM MEMBANGUN SINEGRITAS HUBUNGAN MASYARAKAT DAN MEDIA JURNALISTIK UNTUK MENINGKATKAN MINAT MASYARAKAT PADA PRODUK TABUNGAN EMAS CABANG SIMP. LIMUN KOTA MEDAN - Lita Octaviani; M. Yoserizal Saragih (LPPM Institut Pendidikan Nusantara Global, 2023)
The development of the world economy is now increasing, companies compete to show each other the quality of their goods with other companies, and many consumers begin to invest in any profitable field. Gold investment is a simple form of investment. Because this investment can be done by anyone, whether they are from the educated group or not, by investing in gold in the form of gold coins and gold bars. This study aims to explain the effectiveness of PT. Pegadain in building synergy of public relations and journalistic media to increase public interest in gold savings products at the intersection limun branch in Medan. This research is a qualitative descriptive field research. In collecting data, researchers use interview, observation and documentation techniques. The informants of this study were two employees from PT. Pegadaian branch of intersection lemonade city Medan. After the data is collected, it is processed through a process: editing and description. Then the data was analyzed with Miles and Huberman's data analysis technique. The results obtained in this study that build the synergy of the role of public relations and journalistic media to increase interest using marketing strategies applied by PT. Pegadaian branch of simpang limun kota Medan marketing mix, namely the strategy of advertising programs, sales promotion, and public relations / publicity planned by the management and Pegadaian branch of simpang limun kota Medan succeeded in attracting public interest in Gold Savings products. Thus, the right strategy to attract more customers by developing digital technology, because the media has been loved by many generations because it can be easily accessed anywhere and anytime so that the strategy through digital will be very effective to reach the whole